DETERMINANTS OF REGIONAL TAX REVENUES WITH DOMESTIC INVESTMENT AS MODERATING VARIABLE - Panggabean, Maria Christina; Gunawan, Juniati (LPPM STIE Muhammadiah Bandung, 2024)
Tax revenue received by the government is used to provide infrastructure in each region. A decrease in tax revenue has a negative impact on the provision of public facilities for the society, so that taxes are one of the responsibilities and forms of society contribution to the government. This study was conducted to find out whether gross regional domestic product, the number of manpower, and domestic investment as moderating variables influence regional tax revenue. The population in this study were all provinces in Indonesia with a period of 2017-2022. Sampling using purposive sampling. Data analysis using panel data regression. The amount of data observed is 198 data. The results showed gross regional domestic product, and the number of manpower has a positive influence on regional tax revenue, while domestic investment is not able to moderate gross regional domestic product and the number of manpower on regional tax revenue.